The relationship between modified Graeb score and intraventricular hematoma volume with Glasgow outcome scale and modified Rankin scale in intraventricular hemorrhage of brain: a comparative study - Rashid, Mohammad H.; Hossain, Mohammad N.; Hossain, Muhammad S.; Eva, Israt Z.; Habib, Rumana; Mamun, Abdullah A.; Ahmed, Umam U. (International Journal of Research in Medical Sciences, 2021)
Background: Intraventricular hemorrhage (IVH) is an acute neurosurgical condition. The aim of this study was to identify the relationship between modified Graeb score (mGS) and intraventricular hematoma volume with Glasgow outcome scale (GOS) and modified Rankin scale (mRS). Methods: This is a Quasi-experimental study conducted in the department of neurosurgery, Chittagong Medical College Hospital, Chittagong, Bangladesh during the period from 24 July 2018 to 23 July 2019. After a detailed history and clinical examination, 150 patients were selected for this study. The study participants were divided into two major groups- external ventricular drainage (EVD) and conservative; both groups consisted of 44 patients. Written informed consent were taken from the participants. Data were analyzed using statistical package for the social sciences (SPSS) software. Results: Overall mean age was around 60 years with an age range from 15-85 years. More than three fourth of the patients in both groups were from the age group of >50 years (73.83%). There were no differences between EVD and conservative groups regarding medical comorbidities. Most prevalent comorbidity among the patients of both groups’ hypertension, followed by diabetes and previous ischemic stroke. Overall the most frequent symptoms in the studied patients were vomiting, followed by loss of consciousness, headache and convulsion. There were no significant differences between the two groups regarding presenting symptoms. The mean Glasgow coma scale (GCS) score level was significantly lower in the patients with EVD than their counterpart from 1st post-operative day to 8th post-operative day. However, within-group comparison shows that the GCS score was significantly increased from 1st day to 8th day in both groups of patients. Conclusions: These findings can be used to identify patients in whom an EVD may provide measurable outcomes benefit with respect to patient mortality and help guide neurosurgical decision-making in particular patient subgroups with acute IVH.